ChemInform Abstract: Unusual, Chemoselective Etherification of 2‐Hydroxy‐1, 4‐naphthoquinone Derivatives Utilizing Alkoxymethyl Chlorides: Scope, Mechanism and Application to the Synthesis of Biologically Active Natural Product (.+‐.)‐Lantalucratin C. Issue 27 (16th June 2016) - Ogata, Tokutaro; Yoshida, Tomoyo; Shimizu, Maki; Tanaka, Manami; Fukuhara, Chie; Ishii, Junko; Nishiuchi, Arisa; Inamoto, Kiyofumi; Kimachi, Tetsutaro
Abstract: A new method for the chemoselective etherification of 2‐hydroxy‐1, 4‐naphthoquinone derivatives utilizing alkoxymethyl chlorides is studied.